TANGGUNG JAWAB PERDATA DEBITUR AKIBAT WANPRESTASI TERHADAP PERJANJIAN PINJAMAN ONLINE PADA APLIKASI KREDIVO - Devi, Rizki Cintia; Sudirman, M. (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2025)
The purpose of this study is to determine the default committed by the debtor in the online money loan agreement in the Kredivo application. The method of approach used by the author in this research is normative juridical by examining literature sources. From the results of this study, it is concluded that the first default made by the debtor in the online loan agreement in the Kredivo application is that the debtor does not pay the bills that appear. Defaults that occur are influenced by debtors who forget the due date and the amount of interest that is too large, making it difficult for debtors to pay. The settlement of defaults of online loan debtors in the Kredivo application is by way of litigation and non-litigation. Non-litigation in the form of giving notice of maturity, giving administrative sanctions in the form of late interest fines of 4-6% and then due to the delay it will complicate conventional loans at financial institutions because they will be recorded with the Financial Services Authority (OJK).